Opportunities for self-management in community-based mental health services for patients with schizophrenia - Vähäniemi, Anu (fi=Turun yliopisto|en=University of Turku|, 2018)
As the role of patients in disease management has grown, chronic disease long-term follow-up care and continuity of care between services pose challenges for the health care sector. This study focusses on describing and evaluating opportunities for self-management among patients with schizophrenia in community-based services. The study was carried out in four phases from the perspectives of mental health policy, guidelines and health care personnel. The data was collected between 2012 and 2016. Quantitative and qualitative methods were used to analyse the data. Mental health strategy documents (n=63) were gathered from all municipalities in mainland Finland (n=320) and evaluated with aWHO instrument (Phase I). The documents with the contents related to schizophrenia or psychotic disorder (n=55) were analysed according to topics from the Finnish Current Care Guideline for Schizophrenia (Phase II). Nurses’ attitudes and factors associated with patients with mental illness in community-based services (n= 218) were evaluated with questionnaires (AQ-27) (Phase III). The quality and utilisation of the Finnish Current Care Guideline for Schizophrenia was analysed using the AGREE II instrument by health care personnel (n=49) (Phase IV). Mental health strategy documents were found to have been written, were in the process of being written or were being updated in 223 municipalities. The content and structure of strategies varied and were formulated in different ways. The topics of patient psychosocial rehabilitation and organisation of care were described broadly, but the topics of adherence to treatment, preventive work, physical health, medication and antistigma activities were missing. Positive attitudes of nurses were recognized as enabling mental health work at that level. Being older and having continuing vocational education in mental health training were found to influence the level of positive attitudes. The Current Care Guideline for Schizophrenia can be assumed to utilise planning of care and treatment because the guideline was found to clearly include scope and purpose, various options for management, and evidence-based recommendations. The overall assessment of the guideline by health care personnel was good (72,94%), which supports the utilisation of the guideline. Opportunities for self-management among patients with schizophrenia can be found in community-based services. The guideline for schizophrenia is of high quality, but there is a need for systematic development of selfmanagement implementation, and a reconsideration of all treatment content. The attitudes of nurses were positive toward people with mental illness, but continuing vocational education in mental health issues is still needed. These factors should be stated in the mental health strategies by municipalities regarding the opportunities of self-management.

Skitsofreniapotilaiden itsehallinnan mahdollisuudet perusterveydenhuollossa Viime aikoina terveydenhuollon haasteiksi ovat nousseet kroonisten sairauksien pitkäaikaisseuranta, hoidon jatkuvuus palveluiden välillä sekä potilaiden kasvanut rooli sairauden hallinnassa. Tämän tutkimuksen tavoitteena oli kuvaamalla ja arvioimalla tuottaa tietoa skitsofreniaa sairastavan potilaan itsehallinnan mahdollisuuksista perusterveydenhuollossa. Tutkimus toteutettiin neljässä vaiheessa ja sen näkökulmina olivat mielenterveyspolitiikka, hoitosuositukset ja hoitohenkilökunnan asenteet. Tutkimusaineisto kerättiin vuosina 2012-2016. Väitoskirjassa käytettin sekä maarällisiä että laadullisia aineiston analysointimenetelmiä. Ensin analysoitiin kaikkien mannersuomen kuntien (n=320) mielenterveysstrategiat (n=63) WHO:n mittarin avulla (Vaihe I). Tämän jälkeen kuvattiin, missä määrin skitsofrenian käypä hoito-suosituksen sisältö esiintyi kuntien mielenterveysstrategioissa (n= 55) (Vaihe II). Perusterveydenhuollossa työskentelevien hoitajien (n=218) asenteita mielenterveyspotilaita kohtaan sekä asenteisiin yhteydessä olevia tekijöitä selvitettiin kyselyllä (AQ- 27) (Vaihe III). Lisäksi arvioitiin skitsofrenian käypä hoito-suosituksen laatua ja käytettävyyttä terveydenhuollon henkilöstön (n=49) näkökulmasta AGREE II –mittarin avulla (Vaihe IV). Yhteensä 223 kunnasta joko löytyi mielenterveysstrategia, sellainen oli tekeillä, tai sitä päivitettiin tutkimushetkellä. Strategioiden rakenne ja sisältö kuitenkin vaihtelivat ja ne oli laadittu eri tavoin. Psykososiaalinen kuntoutus ja hoidon organisointi oli kuvattu laajasti, kun taas hoitoon sitoutumista, ennaltaehkäisevää työtä, fyysistä terveyttä, lääkehoitoa ja stigman vähentämistä koskevat aiheet puuttuivat strategioista. Hoitajien valmiudet toteuttaa mielenterveystyötä perustasolla olivat hyvät, sillä heidän asenteensa mielenterveyspotilaita kohtaan olivat positiivisia. Hoitajien iällä ja mielenterveyteen liittyvillä lisäkoulutuksilla havaittiin yhteys hoitajien positiivisiin asenteisiin. Skitsofrenian Käypä hoito -suositusta voidaan hyödyntää hoidon suunnittelussa ja toteutuksessa, koska suosituksen käyttötarkoitus ja erilaiset hoitovaihtoehdot kuvataan siinä selkeästi ja koska se perustuu tutkittuun tietoon. Myös henkilökunnan mahdollisuudet soveltaa suositusta ovat olemassa, sillä henkilökunnan yleisarvio hoitosuosituksesta oli hyvä (72,94%). Tutkimuksen tulokset osoittavat, että perusterveydenhuollosta löytyy skitsofreniaa sairastavien potilaiden hoitoon liittyviä itsehallinnan mahdollisuuksia. Skitsofrenian hoitosuositus oli laadukas, mutta tulevaisuudessa itsehallinnan käyttöönottamiseksi tarvitaan systemaattista kehittämistyötä. Lisäksi hoidossa tarvitaan suosituksen kaikkien osa-alueiden huomioimista. Hoitajien asenteet mielenterveyspotilaita kohtaan olivat positiivisia, mutta mielenterveyteen liittyvää lisäkoulutusta edelleen tarvitaan. Itsehallinnan mahdollistamiseksi nämä asiat tulisi olla kirjattuina kuntien mielenterveysstrategioissa.